GAMBARAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PEMILIK RUMAH SARANG BURUNG WALET DIDESA TOPOYO KECAMATAN TOPOYO - Yunirna, Roswita; Leo, M. Nur Zakariah (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims at 1) Knowing the level of welfare of swallow's nest owners 2) Knowing the level of development of swallow's nest business 3) Knowing the management of swallow nest houses. This research is a qualitative descriptive study. The area that is the object of research is Topoyo Village, Topoyo District, Mamuju Tengah Regency. The population in this study were all swallow nest owners, namely 10 heads of families. Data collecting techniques are carried out through observation, interview and documentation techniques. The results showed that swallow nest owners were generally productive 30-39 years old and all male sexes with marital status were married and the level of education of the average swallow nest homeowner was junior and senior high school graduates. 1) Revenue of the owner of the bird's nest wallet Didesa Topoyo Topoyo Subdistrict Central Mamuju Regency through the indicator of welfare level according to BPS, in 2005 high income that is equal to> 10,000,000 / month or> 120,000,000 / year, based on sales respondents income from swallow nest, namely 13,000,000, - / kg in the harvest period 3-4 times per year as much as> 6 kg in one harvest period or> 234,000,000, - 312,000,000. 2) Increasing the welfare of swallow nest owners can be seen from before and after establishing a swallow nest house, namely. There are (2) respondents who have to pay the loan in the form of installments to the bank so that they have not shown their level of welfare from swallow birds. which causes air pollution and noise pollution.